Memorial: a vida e trajetória docente para o campo - ALVES, Eva Evaristo Ferreira (2023)
The present work has the theme: Life for difficulties where to become a pedagogue, which brings an approach to my student, teaching and academic life, which through the report of my memories about the difficulties that accompany the student. As well as joining a higher education institution, in addition to showing the reality that permeates the student's life in rural areas, which most often do not have their specialties. I will also show the look I have today, in the production of an educator, to reflect on the students' lives. For the construction of this work, I will use a reflective and bibliographic descriptive autobiographical research, seeking to establish a possible relationship between my story and the proposed theme through a qualitative approach, taking into account a dynamic relationship between the subject and the context in which he is inserted. Using as a textual genre the memorial that has been widely used in academic works, which I will theoretically substantiate through PERRENOUD (2002) and FREIRE (1987) and (1996) IMBERNÓN (2010; 2016), PIMENTA (2001), TARDIF (2003, 2012 ), BRASIL (2017), RIOS (2010), as they discuss the reflections proposed in this memorial. It is structured in 7 chapters, in the first I will talk about the beginning of my childhood and entering school, in the second I will talk about elementary school, high school and finally about my professional career, entry and the importance of PARFOR. Finally, I will present the results of this research, thus seeking to recover important facts in the course of my life and on which I can reflect in order to understand my role in the world as a being who needs to fight daily to have my rights respected.